Latent indexation and exchange rate passthrough - Antonio Fiorencio; Ajax Reynaldo Bello Moreira (Institute for Applied Economic Research (ipea), 2015)
This paper uses VAR models to discuss two main questions: a) are the indexing mechanisms that characterised the Brazilian economy for decades a thing of the past, or could they be easily reactivated in the event of some important price shock? b) given the fiscal stance, what would be the likely consequences of a nominal devaluation on inflation, the real exchange rate, real interest rates and unemployment? One of the main results of the paper is tha a possible measure of the degree of indexation of the Brazilian price system was sharply reduced after the Real Plan.
Keywords: 330